2019
DOI: 10.15644/asc53/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Prosthodontic Treatment Modalities for Patients with Periodontally Compromised Anterior Mandibular Teeth: A 2-year follow-up study

Abstract: Objectives To prospectively assess self-perceived chewing function (CF) and oral health-related quality of life (OHRQoL) in geriatric patients after receiving three different treatment modalities in the mandible: removable partial denture (CD-RPD), complete denture (CDs), or complete overdenture supported by mini dental implants (CD-MDI). At baseline, all patients had mobile anterior teeth (1 mm or >) and missing posterior teeth in the mandible. Patients were completely edentulous in the maxilla. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…It has been also reported that mandibular ODs supported by four MDIs lead to a long‐lasting treatment‐induced improvement in oral health‐related quality of life (Čelebić et al, ; Reissmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that mandibular ODs supported by four MDIs lead to a long‐lasting treatment‐induced improvement in oral health‐related quality of life (Čelebić et al, ; Reissmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the edentulous area in the anterior tooth region preferred removable partial denture, whereas implant-supported overdenture led to significant improvement in the chewing function. [ 11 12 13 ] Even though, chewing competency and dietary status signify when insufficient dentition edentulous state is amended with partial/complete dentures; masticatory function in these rehabilitation prostheses is less efficient in comparison to the original intact natural teeth. Hence, it is the foremost duty of the dentist to maintain the natural dentition by carrying out various prophylactic measures along with giving instructions for maintaining the overall oral and general health.…”
Section: Discussionmentioning
confidence: 99%
“…Oral biofilm and periodontal parameters are reported to be influenced by all the appliances that are in contact with mucosa for many hours per day, such as prosthodontic frameworks [34] and orthodontic appliances [35] or continuous chewing of substances [36].…”
Section: Discussionmentioning
confidence: 99%